Developing a New Tool for Early Detection of the Nutritional and Health Risk Factors of Urban Workers’ Productivity - Nai, Hildagardis Meliyani Erista; Estri, Arimbi Karunia; Widianti, Christina Ririn (UI Scholars Hub, 2023)
Nutrition and health play vital roles in work productivity. This study aimed to develop a risk self-assessment tool called Early Detection of the Nutritional and Health Risk Factors on the productivity of urban workers. This study was conducted in two stages: 1) the development of the tool to determine the nutritional and health risk factors that affect productivity based on literature reviews and scoring systems and 2) the testing of validity and reliability. Finally, the tool contained 63 items, including 28 items on nutritional risk factors and 35 on health risk factors. The validity of the tool was assessed using the content validity index (CVI): item-level CVI (I-CVI) and scale-level CVI (S-CVI), and face validity index (FVI) and reliability using Cronbach’s alpha coefficient. Preliminary versions of this tool showed a high content validity (I-CVI = 1.00; S-CVI based on the average method = 1). The face validity index among urban workers was at least 0.90, and the overall Cronbach’s alpha coefficient was 0.70. The tool developed is acceptable, but revisions are still needed, and sample sizes must be increased.